Experimental study on the cyclic behavior of integrated panels for cold-formed steel shear wall system - Lee, Doo Yong; Cho, Bong Ho; Jung, Dam I.; Lee, Jae Sub; Lee, Keun Woo (Applied Sciences (Switzerland), 2020)
Studies on the constructability of cold-formed steel (CFS) members are lacking. In this context, this paper proposes an integrated panel to replace the studs and steel sheet in the steel-sheathed wall system used in light gauge steel frames. The integrated panel was developed, to not only exhibit better structural performance and constructability than the steel-sheathed wall system, but to also reflect the appropriate details for applications to on-site panel construction. Cyclic loading tests were performed to investigate the seismic performances of three integrated panel specimens and a steel-sheathed panel specimen. The integrated panel specimens exhibited greater deformation capacity, ductility and equivalent damping ratio than the steel-sheathed panel. Although the web slenderness of the integrated member was nearly 400, the nominal strength of the integrated panel was predictable on an AISI standard. However, for stud-reinforced integrated panels, the nominal strength was overestimated by 45%-60%, and a draft equation was proposed to predict the yield strength of these panels. The proposed equation accurately predicted the yield strength of the stud-reinforced integrated panel specimens. The study results can aid in the construction of light gauge steel frames that require reinforcing parts with a high web slenderness ratio.
Keywords: cold-formed steel shear wall system; cyclic tests; integrated panel; light gauge steel frame; steel panel; structural performance